Lymphocyte subpopulations of bone marrow of breast cancer patients - T. A. Grigorieva; O. A. Beznos; N. N. Tupitsyn; I. K. Vorotnikov; V. Yu. Selchuk; D. A. Ryabchikov (ABV-press, 2015)
We have studied bone marrow lymphocytes subpopulations in 67 patients with breast cancer and 13 patients with benign processes in the mammary gland. Morphological study of the cellular composition of the bone marrow and immunological analysis of lymphocyte subpopulations have been done. Comparative characterization of lymphocyte subpopulations in the bone marrow of patients with breast cancer and benign breast diseases was done by flow cytometry. The gate of Mature lymphocytes (CD45++) studied subpopulations of T cells (CD3), b cells (CD19), NK cells (CD56+CD3-). Among T lymphocytes (CD3+) was studied TCRγδ and TCRαβ cells, a subpopulation of CD4, CD8, CD4+, CD25+ T-regulatory cells. Within В-lymphocytes (CD19+) was studied subpopulations CD10, CD38, CD5 lymphocytes. We revealed a significant increase of CD5+, CD38+ B-cells in patients with breast cancer compared to benign tumors. Index of maturation of erythrocytes was significantly higher in BC 0.96 in comparison with benign processes 0.92. When comparing immunological data with histological structure of the tumor in the group of breast cancer patients, it was noted that the percent of CD10+ B-lymphocytes was significantly higher in infiltrative ductal cancer in comparison to infiltrative lobular carcinoma (19.3 and 8.0 % accordingly; p = 0.024).